2010
DOI: 10.1063/1.3365064
|View full text |Cite
|
Sign up to set email alerts
|

Magnetostructural transition in Ce(Fe0.975Ga0.025)2 compound

Abstract: The magnetic and magnetostructural properties of the polycrystalline Ce(Fe 0.975 Ga 0.025 ) 2 have been investigated as a function of temperature and magnetic field. In Ce(Fe 0.975 Ga 0.025 ) 2 the magnetic transition from antiferromagnetic (AFM) to ferromagnetic state (FM) is accompanied by a structural transformation from rhombohedral to cubic structure. Phase coexistence is present during both the temperature and field driven transformations from the AFM to FM phase.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…4 Such a phase co-existence is also observed in magneto-structural studies in doped CeFe 2 . 5 While there are many studies on the effect of purely chemical disorder on the metamagnetic transition, 6,7 it is not clear how crystalline defects influence this transition. Crystalline defects can be easily introduced by fast neutron or ion irradiation.…”
Section: Introductionmentioning
confidence: 99%
“…4 Such a phase co-existence is also observed in magneto-structural studies in doped CeFe 2 . 5 While there are many studies on the effect of purely chemical disorder on the metamagnetic transition, 6,7 it is not clear how crystalline defects influence this transition. Crystalline defects can be easily introduced by fast neutron or ion irradiation.…”
Section: Introductionmentioning
confidence: 99%
“…Our previous XRD studies in magnetic field have shown that the sample completely transforms from rhombohedral to cubic on application of magnetic field. 8 Therefore, we have analyzed the data at T ¼ 30 K in 60 kOe field using Fd 3m space group. The ferromagnetic moment is confined to Fe alone.…”
Section: Resultsmentioning
confidence: 99%
“…3,7 Temperature and field variations of x-ray diffraction (XRD) analysis on this system clearly establish the fact that antiferromagnetic phase transition is associated with a structural phase transformation from cubic to rhombohedral phase. 8 By comparing various dopants that stabilize the low temperature AFM state, we have found that Si doping causes better stabilization of the AFM state. Though there are a few reports on the magnetic structures of other doped CeFe 2 compounds, 6 no such reports are available on Si doped compounds.…”
Section: Introductionmentioning
confidence: 93%
“…In addition, the magnetic and electronic properties reveal particularly flexible in terms of saturation magnetization, ordering temperature, and type of transition order. The RFe 2 series exhibit ferri-magnetic arrangements with rather high ordering temperatures (second order type) and compensation points when M R (T) = −M TM (T) [20][21][22][23]. Interestingly, in the RCo 2 binaries, the magnetic polarization on Co is typically driven by its itinerant electron character leading to rather low ordering temperature that was reported being of first order type [15].…”
Section: Introductionmentioning
confidence: 85%